Effectiveness of Insecticide Treated Mosquito Nets on the Death of Anopheles subpictus Mosquitoes - Ety Rahmawati; Johanis JP Sadukh; Oktofianus Sila (Jurnal Penelitian Pendidikan IPA, 2024)
The prevalence of malaria in East Nusa Tenggara based on positive diagnosis results containing malaria parasites and symptoms in the 2013 - 2015 period decreased but has not yet reached the National Strategic Plan target, namely in 2013 it was 21 per 1,000 population (o/oo), in 2014 it was 14 o/oo, and in 2015 it became 8 o/oo (NTT Health Office, 2016). In 2017 there was a spike in malaria cases to 211,409 cases (API = 44.96 o/oo). Kupang Regency with 1,108 cases (API = 24.87 o/oo). Malaria cases in the Tarus Community Health Center work area are the eighth highest, namely 7 cases. This study aims to analyze the effectiveness of insecticide-treated bed nets on the death of Anopheles subpictus mosquitoes. The variables observed were the length of time the mosquito net was used, the frequency of washing the mosquito net, the method of washing the mosquito net, and the percentage of Anopheles subpictus mosquito deaths. The effectiveness of insecticide-treated bed nets on the death of Anophles subpictus mosquitoes with usage time < 3 years (100%), usage time 3 – 5 years (70%) and usage time > 5 years (40%). The effectiveness of insecticide-treated bed nets that have never been washed reaches 100% mortality within 24 hours of observation. Meanwhile, mosquito nets with a washing frequency of 1 – 10 times (70%) kill mosquitoes, and a washing frequency of > 10 times (50%). The method of washing mosquito nets carried out by the community in the Puskesmas Working Area is 100% using detergent. In the control group that used mosquito nets that did not contain insecticide, no Anopheles subpictus mosquito deaths occurred (0%). Suggestions for health workers to increase education regarding the correct use of mosquito nets, so that a higher level of effectiveness of mosquito nets is obtained as a means of personal protection in avoiding mosquito bites.